Hyaline cartilage at the portal plate and gallbladder in biliary atresia - Rajasekaran, Sangamitra; Neupane, Hari; Bawa, Monika; Saikia, Uma Nahar; Lal, Sadhna; Mitra, Suvradeep (Autopsy and Case Reports, 2024)
Biliary atresia (BA) is a fibro-obliterative cholestatic disease of infancy. The presence of cartilage in the resected tissue is an uncommon finding. We documented the presence of both mature and immature hyaline cartilage in the portal plate and the wall of the gallbladder in a 2-month-old girl infant with BA who had undergone Kasai portoenterostomy. The presence of cartilage could be part of a heterotopia or an uncommon connective tissue metaplasia. The presence of immature cartilage with the merging of the perichondrium with the soft tissue highlights a metaplastic etiology in the index case.